Interstitial ectopic pregnancy - two case reports of early diagnosis and conservative management - Lourenço,Inês Vermelho (2021)
Abstract Interstitial ectopic pregnancy is rare, but can cause severe complications. The diagnosis is challenging and the optimal treatment varies according to each case. The authors present two case reports of early interstitial pregnancies diagnosed in asymptomatic or mildly symptomatic women. One was submitted to laparoscopic excision of the ectopic mass without complications. As for the other, she was treated with intramuscular methotrexate. In both cases, human chorionic gonadotropin decreased consistently until it became undetectable 4 weeks after treatment. An early and accurate diagnosis is fundamental to avoid major complications. Conservative treatment is possible and should be recommended in selected cases.